New options for cilostazol-based dual antiplatelet therapy for ischaemic stroke prevention in East Asian populations: a systematic review and meta-analysis - Wang, Xiaorui; Wang, Yixin; Zheng, Qiang; Li, Pengwei; Yin, Jingli; Wang, Miaomiao; Zou, Liangyu; Wang, Jie; Pan, Jialin; Qin, Lei; Luo, Song; Yang, Lijuan (Frontiers in Pharmacology, 2025)
Background and purposeThe objective of this study is to systematically review the efficacy and safety of cilostazol-based dual antiplatelet therapy (DAPT) in patients with stroke.MethodsTwo reviewers conducted a comprehensive search of eligible studies published in PubMed, Medline, the Cochrane Library, Embase, and four Chinese databases from their establishment to 31 July 2024. The review was registered (CRD42024559047).ResultsThis study included a total of 4,473 subjects from 11 studies. The results indicated that, when compared to aspirin/clopidogrel single antiplatelet therapy (SAPT), cilostazol-based DAPT was associated with lower ischemic stroke (RR = 0.54, 95% CI 0.38–0.75, P = 0.0003) and any stroke recurrence (RR = 0.52, 95% CI 0.31–0.86, P = 0.01). Furthermore, the incidence of general adverse events was higher in the cilostazol-based DAPT (RR = 1.93, 95% CI 1.16–3.21, P = 0.01), while no statistically significant difference was observed between the two groups with regard to serious adverse events. The subgroup analysis of follow-up time revealed that the cilostazol-based DAPT regimen demonstrated superior efficacy in reducing the incidence of ischemic stroke recurrence (RR = 0.51; 95% CI 0.36–0.73; P = 0.0002) and any stroke recurrence (RR = 0.49; 95% CI 0.35–0.67; P < 0.0001) in the long-term (>3 months) versus the short-term (≤3 months) group. Furthermore, the cilostazol-based DAPT regimen did not increase the risk of serious adverse events.ConclusionDAPT combined with cilostazol and aspirin or clopidogrel was superior to aspirin or clopidogrel alone, did not increase serious adverse events, and was more effective for long-term (>3 months) prophylaxis.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024559047